On the calculation of volume. IV - Balle, Solvej, 1962- (New Directions paperbook., 2026)
"...Book IV heralds the arrival of many others, and soon to be even more, roaming uncertainly through the same November day. Could this be the first stirrings of an alternate civilization? The big house in Bremen turns into the headquarters for this growing group of time-trapped individuals. But who are they and what has happened to them? Are they loopers, repeaters, or returners? A brilliant modern spin on the myth of Babel in the Book of Genesis, Book IV asks urgent questions concerning the naming of things, of people, and of the functions of language itself--must a social movement have a common language in order to exist? Snatches of conversation, argument, and late-night chatter crowd onto the pages of Tara's notebooks. Amid the buzz and excitement of a new social order coming into being, Book IV ends with a sudden, unexpected, and tantalizing cliffhanger that no one--not even Tara, our steady cataloger and cartographer of the endless November day--could have foreseen."--Provided by publisher.